Monitoring of cerebral blood flow during hypoxia‐ischemia and resuscitation in the neonatal rat using laser speckle imaging. Issue 7 (14th April 2016) - Wood, Thomas; Smit, Elisa; Maes, Elke; Osredkar, Damjan; Falck, Mari; Elstad, Maja; Thoresen, Marianne
Abstract: Neonatal hypoxic‐ischemic encephalopathy (HIE) is associated with alterations in cerebral blood flow (CBF) as a result of perinatal asphyxia. The extent to which CBF changes contribute to injury, and whether treatments that ameliorate these changes might be neuroprotective, is still unknown. Higher throughput techniques to monitor CBF changes in rodent models of HIE can help elucidate the underlying pathophysiology. We developed a laser speckle imaging (LSI) technique to continuously monitor CBF in six postnatal‐day 10 (P10) rats simultaneously before, during, and after unilateral hypoxia‐ischemia (HI, ligation of the left carotid artery followed by hypoxia in 8% oxygen). After ligation, CBF to the ligated side fell by 30% compared to the unligated side ( P < 0.0001). Hypoxia induced a bilateral 55% reduction in CBF, which was partially restored by resuscitation. Compared to resuscitation in air, resuscitation in 100% oxygen increased CBF to the ligated side by 45% ( P = 0.033). Individual variability in CBF response to hypoxia between animals accounted for up to 24% of the variability in hemispheric area loss to the ligated side. In both P10 and P7 models of unilateral HI, resuscitation in 100% oxygen did not affect hemispheric area loss, or hippocampal CA1 pyramidal neuron counts, after 1‐week survival. Continuous CBF monitoring using LSI in multiple rodents simultaneously can screen potential treatment modalities that affect CBF, and provide insight into the pathophysiology of HI. Abstract : The extent to which cerebral blood flow (CBF) changes contribute to neonatal hypoxic‐ischemic (HI) brain injury is still unknown. We developed a laser speckle imaging (LSI) technique to simultaneously and continuously monitor CBF in six postnatal‐day 10 rats before, during, and after unilateral hypoxia‐ischemia. Compared to resuscitation in air, resuscitation in 100% oxygen increased CBF to the ligated side by 45%, with no overall effect on pathology. Individual variability in CBF response to hypoxia accounted for up to 24% of the variability in injury between animals.